Eksistensi Makam Syekh Burhanuddin : Studi tentang Sistem Religi Masyarakat di Nagari Manggopoh Palak Gadang - Oksa Putra Nurman; Annisa Tul Muharrara (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study discuss about exsistence of Syekh Burhanuddin tomb: a study of society’s religious systems at Nagari Maggopoh Palak Gadang, Kecamatan Ulakan Tapakis, Kabupaten Padang Pariaman. The purpose of this study was to learn of Syekh Burhanuddin tomb as a religious system in Nagari Maggopoh Palak Gadang and also to understand how the ritual processions on the tomb looked. The theory used in this study is of exsistensialism and religion. The exsistence of the Sheiks Burhanuddin tomb is how the tomb can still survive to this day as a religious system in the midst of society. The method used is qualitative research with an ethnographic approach. Data collection techniques are observation, interviews, library studies and documentation. As for the finding in this study, the public believes by pilgrimage to the grave we can receive blessings and want help through a medium of grave and grave meditation became something that society in particular decided upon. In addition to visiting the Syekh Burhanuddin tomb was believed by the local people and tarekat Syattariyah that a visit to the sepulchre would bring blessings from the Syekh Burhanuddin. The culture is made into reality in the midst society, and it being something the cult.